An aggressive clinical course of polycythemia vera with coexisting complications: a case report - Kanuga, Kshitij H.; Arora, Anoushka; Dhruva, Yashraj (International Journal of Research in Medical Sciences, 2025)
Polycythemia vera (PV) is a myeloproliferative disorder characterized by rapid proliferation of red blood cells. It may present with symptoms of hyper viscosity. Complication of thrombosis is well recognized, but its rapid progress and coexistence of involvement of various organ sites simultaneously are not seen as often. We present a case of a 40-year-old female who was incidentally diagnosed with PV due to her presentation with extrahepatic portal venous obstruction (EHPVO). Her elevated platelet count prompted a bone marrow biopsy, leading to the finding of Janus kinase-2 (JAK2)-positive PV. Her condition rapidly progressed to decompensated chronic liver disease, likely triggered by the portal hypertension due to EHPVO. This was further complicated by her PV progressing to myelofibrosis, a rare complication of PV. This progression typically occurs after 10-15 years of diagnosis, but in this case, it was seen within 3 years, demonstrating the rapid course of her disease. This case is noteworthy for how differently PV can present. It highlights the importance of investigating patients for underlying blood malignancies when they present with clots without any identifiable cause. It also sheds light on how fast this disease can progress and shows the importance of early diagnosis and appropriate management to prevent several complications associated.